Multicenter validation of CSF neurofilaments as diagnostic biomarkers for ALS. Issue 5 (17th August 2016) - Oeckl, Patrick; Jardel, Claude; Salachas, François; Lamari, Foudil; Andersen, Peter M.; Bowser, Robert; de Carvalho, Mamede; Costa, Júlia; van Damme, Philip; Gray, Elizabeth; Grosskreutz, Julian; Hernández-Barral, María; et al.
Abstract: OBJECTIVE: Neurofilaments are leading neurochemical biomarkers for amyotrophic lateral sclerosis (ALS). Here, we investigated the effect of preanalytical factors on neurofilament concentrations in cerebrospinal fluid (CSF) in a "reverse" round-robin with 15 centers across Europe/U.S. METHODS: Samples from ALS and control patients (5/5 each center, n = 150) were analyzed for phosphorylated neurofilament heavy chain (pNfH) and neurofilament light chain (NfL) at two laboratories. RESULTS: CSF pNfH was increased ( p < 0.05) in ALS in 10 out of 15 centers and NfL in 5 out of 12 centers. The coefficient of variation (CV%) of pNfH measurements between laboratories was 18.7 ± 19.1%. We calculated a diagnostic cut-off of >568.5 pg/mL for pNfH (sensitivity 78.7%, specificity 93.3%) and >1, 431pg/mL for NfL (sensitivity 79.0%, specificity 86.4%). CONCLUSION: Values in ALS patients are already comparable between most centers, supporting eventual implementation into clinical routine. However, continuous quality control programs will be necessary for inclusion in the diagnostic work-up.